SISTEM INFORMASI PENILAIAN INDEKS KINERJA DOSEN UNIVERSITAS SAHID SURAKARTA - Septo Putra, Andri Wahyu; Anwariningsih, Sri Huning; Suryono, Suryono (2086-4221, 2013)
Products resulting from this study is an assessment  sistem  based index of faculty performance objects, which built the  sistem adjusts needs assessment of faculty performance. Features presented in information sistems, among others, provide ease of student  teacher performance appraisal, assessment feedback from faculty, students input data, and the ease of report generation. After testing by the method of McCall, this sistem  scored 74.14% of total quality. Thus the results of such testing, the  sistem  is expected to facilitate the processing of data and presenting information so that it can be applied to the University of Sahid Surakarta.